Patricia Hill Collins’ concepts of intersectionality and Stephen Lukes’ concepts of power in the sociological understanding of political correctness - Nekhaienko, Oksana (Eastern Review, 2021)
The article actualizes the issue of political correctness and the need to develop tools for its further study. Political correctness is considered in the context of gender studies and power relations. The concept of attitudes towards political correctness is revealed, and an attempt is also made to reveal the mechanism of the formation of linguistic attitudes in the mass consciousness through the prism of the concepts of Stephen Lukes and Patricia Hill Collins. The historical and theoretical foundations of the formation of intersectionality are also considered. Intersectionality is focused on the study of hierarchical differences between individuals and groups, depending on the complex intersections of their position in society, determined by many parameters. Respectively, the intersectional approach to the analysis of power and language allows us to solve a number of methodological difficulties associated with the combination of macro and micro levels, which makes possible the further empirical analysis of political correctness directly as a social phenomenon, while taking it out of the linguistic sphere. Political correctness is studied as a formal embodiment of intersectionality, taking into account all the features of cross-identity in linguistic practices. The use of the intersectional method makes it possible to reveal political correctness not only as speech prescriptions, but as a multi-component phenomenon that must be considered in close connection with various kinds of discrimination. The role of power, as the main element, in the mechanisms of interiorization of attitudes towards political correctness is revealed. We highlight the role of symbolic power in ensuring voluntary consent, which is the basis for political correctness and ensures its relatively stable nature. The possibility of using discourse analysis as one of the main methods of studying political correctness is substantiated.